An Arctic encounter with Indigenous and non-Indigenous youth as pedagogy for historical consciousness and decolonizing - McGregor, Heather E. (2020)
PLEASE CITE AS: McGregor, H. E. (2018). An Arctic encounter with Indigenous and non-Indigenous youth as pedagogy for historical consciousness and decolonizing. Historical Encounters: A journal of historical consciousness, historical cultures, and history education, 5(1), 90-101. Available at: http://hej.hermes-history.net/index.php/HEJ/article/view/101 In this article I reflect on a pedagogical encounter that occurred during my research with a program called Students on Ice, a ship-based expedition to the Arctic with youth and adults, including a large number of Indigenous Northerners. Together, we visited a National Historic Site and confronted part of Canada’s history of colonization. I frame this powerful pedagogical encounter with Dwayne Donald’s (2012) theory of decolonizing education, wherein processes of decolonizing and historical consciousness are deeply linked. I work to identify the dimensions of this encounter that produced such a powerful learning opportunity in service of both historical consciousness and decolonizing. I found that as students learned how people are differentlyhistorically conditioned, they did not resort to voyeuristic distance, but rather recognition of connection, and from that, “ethical relationality” (Donald, 2012) may flow.